1997
DOI: 10.1128/jb.179.23.7507-7514.1997
|View full text |Cite|
|
Sign up to set email alerts
|

Escherichia coli cells expressing a mutant glyV (glycine tRNA) gene have a UVM-constitutive phenotype: implications for mechanisms underlying the mutA or mutC mutator effect

Abstract: Transfection of M13 single-stranded viral DNA bearing a 3,N 4-ethenocytosine lesion into Escherichia coli cells pretreated with UV results in a significant elevation of mutagenesis at the lesion site compared to that observed in untreated cells. This response, termed UVM, for UV modulation of mutagenesis, is induced by a variety of DNA-damaging agents and is distinct from known cellular responses to DNA damage, including the SOS response. This report describes our observation, as a part of our investigation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
61
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(68 citation statements)
references
References 31 publications
(37 reference statements)
7
61
0
Order By: Relevance
“…One possible explanation for this could be mistranslationinduced error-prone replication leading to an increased mutation rate, a phenomenon described in Escherichia coli (18,19). To test whether this was the case, we sequenced the RRDR of rpoB and found that 24/24 of the EMED colonies isolated from media containing rifampicin were WT in sequence.…”
Section: High Mycobacterial Mistranslation Results In Rifampicin Phenmentioning
confidence: 99%
“…One possible explanation for this could be mistranslationinduced error-prone replication leading to an increased mutation rate, a phenomenon described in Escherichia coli (18,19). To test whether this was the case, we sequenced the RRDR of rpoB and found that 24/24 of the EMED colonies isolated from media containing rifampicin were WT in sequence.…”
Section: High Mycobacterial Mistranslation Results In Rifampicin Phenmentioning
confidence: 99%
“…In addition to the well-known Escherichia coli SOS system, emerging evidence suggests the existence of a number of such pathways in E. coli (7). One of the more intriguing newly recognized mutagenic pathways is the one elicited in mutA cells (7,16,27), in which the expression of an altered glyV glycine tRNA gene results in a strong mutator phenotype (27) characterized by elevation of transversions. In the mutA allele, the normal 3Ј-CCG anticodon is mutated to a 3Ј-CUG anticodon such that the mutant tRNA misreads the aspartate codon 5Ј-GAU/C as glycine at a low efficiency.…”
mentioning
confidence: 99%
“…Expression of the mutA phenotype is constitutive and requires the recA and recB genes, but not umuD, umuC, dinB, or other lexA-repressible functions (16,23), and thus represents a novel inducible mutagenic pathway termed "translational stress-induced mutagenesis" (TSM) (7).…”
mentioning
confidence: 99%
See 2 more Smart Citations